SUMARNI'S PERSEVERANCE IN PURSUING FINANCIAL INDEPENDENCE - Manurung, Ontje (Sekolah Tinggi Bahasa Asing LIA Yogyakarta, 2024)
Abstract Sumarni, the protagonist in the novel Entrok by Okky Madasari is portrayed as an independent and an ambitious woman. Throughout the novel, Sumarni faces various challenges in her efforts to gain financial independence, however, her perseverance asserts her individuality and challenge the limitations imposed by her community. The objectives of this study is to find out the factor, challenges, and ways to cope with the challenges in pursuing financial independence. The study uses a descriptive analysis method and applies Structural approach. The result of the study shows that personal ambition is the factor that drives Sumarni to pursue financial independence. In pursuing financial independence, Sumarni encounters challenges from the society, her daughter, and corrupted army. The challenges from the society and her daughter are manifested in the gender wage disparity and social stigma and treatment to money lender or loan shark and the challenges from the corrupted army is manifested in political oppression. Sumarni copes with the challenges against gender wage disparity by rejecting destiny which is realized by working as a porter. The challenges from the society and her daughter are coped with two ways, one is by confronting the oppositions directly and the other one is by giving no response and doing self-talk. The way how Sumarni copes with the corrupted army is by confronting and paying protection money. Keywords: Entrok, ambition, perseverance, financial independence